2014
DOI: 10.1177/0269215514556299
|View full text |Cite
|
Sign up to set email alerts
|

The safety and feasibility of an intervention to improve balance dysfunction in ambulant adults with cerebral palsy: a pilot randomized controlled trial

Abstract: A customised balance programme is feasible and safe for ambulant adults with cerebral palsy. Small effects from balance training in selected outcomes occurred. Study replication with at least 38 participants per group to confirm efficacy is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(47 reference statements)
0
12
0
Order By: Relevance
“…The four remaining studies showed no statistically significant differences and trivial effect sizes between the control and experimental groups. 11,14,16,17 Although not all studies demonstrated statistical significance in their interventions, some of the studies reported clinical significance in other areas. Kim and colleagues 15(p.912) discussed the fact that participants also showed improvements in functional ''gait measures such as cadence, walking velocity, stride length, step length, stride time, and step time.''…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The four remaining studies showed no statistically significant differences and trivial effect sizes between the control and experimental groups. 11,14,16,17 Although not all studies demonstrated statistical significance in their interventions, some of the studies reported clinical significance in other areas. Kim and colleagues 15(p.912) discussed the fact that participants also showed improvements in functional ''gait measures such as cadence, walking velocity, stride length, step length, stride time, and step time.''…”
Section: Discussionmentioning
confidence: 99%
“…11,[15][16][17] Regarding blinding, the care provider was not blinded in any of the studies reviewed, 11,14-18 and the patient was not blinded in four of the randomized studies; 11,14,16,17 this could lead to bias on the part of care providers and patients. No disclosure of information about co-interventions could decrease assurance that the results of a study occurred solely because of that intervention and not secondarily, because of external factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations